163k views
4 votes
Solve the system by substitution


y= 7x

x-7y= -48

User Opal
by
5.8k points

2 Answers

8 votes

Final answer:

The system is solved by substituting the expression for y from the first equation into the second. Solving for x and then y, the solution is found to be x=1 and y=7.

Step-by-step explanation:

To solve the system by substitution, you can take the expression for y from the first equation and substitute it into the second equation. The first equation y=7x allows us to understand that wherever we see a y in the second equation, we can replace it with 7x. So the second equation x-7y=-48 becomes x-7(7x)=-48, which simplifies to x-49x=-48 or -48x=-48. Solving for x we get x=1. Plugging this back into the first equation to find y, we get y=7(1)=7. Hence, the solution to the system is x=1 and y=7.

User Sharathi RB
by
5.5k points
7 votes

Answer:

x - 7(7x) = -48

x - 49x = -48

-48x = -48

x = 1

Step-by-step explanation:

hope this helps

User Hongyang Du
by
6.1k points